KINETIC SPECTROPHOTOMETRIC METHODS FOR THE DETERMINATION OF AMOXICILLIN IN PHARMACEUTICAL PREPARATION - Al-Abachi, Mouayed; Abdul Sattar, Jwan (Iraqi Journal of Science, 2024)
Two simple, sensitive and economical kinetic spectrophotometric methods have been developed for the estimation of Amoxicillin in pure form and pharmaceutical preparations.The methods based on the oxidation of the studied drug by a known amount of potassium permanganate in alkaline medium and subsequent determination of manganate ion(Method A)and unconsumed potassium permanganate(Method B),at a suitable λmax=602 and 524 nm,respectively.The reacted oxidant was found to be corresponding to the drug content. The initial rate and fixed time (at 30 minutes) methods are utilized for construction of calibration graphs to determine the concentration of the studied drugs. The calibration graphs are linear in the concentration ranges of (0.5–9.0) μg.ml−1 and (1-11) μg.ml−1 using the initial rate and fixed time methods, respectively. The results are validated statistically and checked through recovery studies. The two methods have been successfully applied for the determination of the studied Amoxicillin in commercial dosage form.